Outdoor temperature and its effect on mortality in South Africa - Scovronick, N.; Wright, C.Y.; Garzena, D.; Sera, F.; Fratianni, S.; Acquaotta, F.; Gasparrini, A. (Clean Air Journal = Tydskrif vir Skoon Lug, 2018)
Researchers from the USA, UK, Italy and South Africa recently conducted the first long-term, nation-wide study of the association between outdoor temperature and mortality in South Africa. Overall, the authors identified a U-shaped relationship, indicating that the risk of mortality increases from exposure to both heat and cold. Mortality risks were highest in children and the elderly, whereas no relationship was found in people aged 25-44 years. Over the full study period (1997-2013), roughly 3.4% of all deaths in the country were attributable to non-optimum temperatures, with much of the burden occurring on days with relatively moderate outdoor temperatures.